Обнаружение эктопаразита Argulus coregoni (Crustacea: Branchiura) в р. Казанке (бассейн Куйбышевского водохранилища, Республика Татарстан, РФ) - Яковлев, В.А.; Кашеваров, Г.С.; Хабибуллина, Г.И. (Гидробиологический журнал, 2013)
Эктопаразит лососевых рыб Argulus coregoni был обнаружен в июне 2010 г. в среднем течении р. Казанки — левого притока Куйбышевского водохранилища (Республика Татарстан, РФ). Наряду с рассмотрением географического распространения вида обсуждаются пути проникновения и условия, способствующие возможности существования паразита в реке. Ектопаразита лососевих риб Argulus coregoni було знайдено в червні 2010 р. в середній течії р. Казанки — лівої притоки Куйбишевського водосховища (Республіка Татарстан, РФ). Поряд із розглядом географічного поширення виду обговорюються шляхи проникнення та умови, що сприяють можливості існування паразита в річці. In June, 2010, an ectoparasite, fish louse, Argulus coregoni was found on the middle part of the Kazanka River, left inflow of the Kuybyshev Water Reservoir (Republic Tatarstan, Russia). As the fish-breeding factory located at riverhead has started to grow up trout, Salmo gairdneri Richardson, last years, it is possible to consider that most probably the parasite has penetrated into the river from the fish farm. As there are no Salmonidae fishes in the river, the given finding allow to assume that the conditions of an inhabitancy in river are favorable, and the parasite is capable to pass full life cycle, parasitizing on other fishes, most likely, on Cyprinidae or Percidae fishes.